Nilai Integrasi Islam pada Mata Kuliah Keterpaduan Islam dan Sains - Eko Wahyu Nur Sofianto; Ratna Kartika Irawati (CV Najmi Edu Creative, 2025)
This study explores the contextual integration of Islamic values within science education through the